2000
DOI: 10.1038/35015017
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the calcium pump of sarcoplasmic reticulum at 2.6 Å resolution

Abstract: Calcium ATPase is a member of the P-type ATPases that transport ions across the membrane against a concentration gradient. Here we have solved the crystal structure of the calcium ATPase of skeletal muscle sarcoplasmic reticulum (SERCA1a) at 2.6 A resolution with two calcium ions bound in the transmembrane domain, which comprises ten alpha-helices. The two calcium ions are located side by side and are surrounded by four transmembrane helices, two of which are unwound for efficient coordination geometry. The cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

121
2,109
5
22

Year Published

2001
2001
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,759 publications
(2,257 citation statements)
references
References 47 publications
121
2,109
5
22
Order By: Relevance
“…As it was unambiguously demonstrated by previous binding measurements [7] and crystallographic analysis [11] that SERCA binds two Ca 2+ per mole, we refer to this value as 100% saturation, and show in Fig. 2 …”
Section: Binding and Atpase Measurementsmentioning
confidence: 67%
See 2 more Smart Citations
“…As it was unambiguously demonstrated by previous binding measurements [7] and crystallographic analysis [11] that SERCA binds two Ca 2+ per mole, we refer to this value as 100% saturation, and show in Fig. 2 …”
Section: Binding and Atpase Measurementsmentioning
confidence: 67%
“…(10) (11) where N S is the total concentration of SERCA molecules. Since the measured Ca 2+ binding isotherms for SERCA are normalized with respect to the maximum saturating values, for comparison the calculated results also need to be expressed as normalized Ca 2+ binding curves.…”
Section: Proposed Statistical Mechanics Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the binding sequence of Na + this site would be related to the second ion bound. The first Na + ion is assumed to bind to a site formed by transmembrane ␣-helices (which could be M4-M6 and M8 according to [37]). In the case of Na,K-ATPase this site is not accessible for di-or trivalent cations.…”
Section: Discussionmentioning
confidence: 99%
“…Menguy and collaborators suggested that the cytoplasmic loop located between transmembrane segments 6 and 7, L6/7, controls the access to the first and second Ca 2+ binding site, and that this process could be related with the occlusion of the first Ca 2+ by a movement of the L6/7 over the first site, thus opening the second [24]. The recent publication of the crystal structure of the SR Ca-ATPase has proven the side by side binding of Ca 2+ ions, although the loop L6/7 has been given a different assignment as to how it affects Ca 2+ binding [37]. Due to the To determine the half-saturating Na + concentrations, K Na , the experiments were fitted with Hill functions (Eq.…”
Section: Binding Of Na + In the Absence Of Other Cationsmentioning
confidence: 99%